Amylose content and RVA profile characteristics of noodle rice under different conditions. (10th January 2020) - Xuan, Ying; Yi, Yang; Liang, He; Wei, Shanqing; Chen, Nianping; Jiang, Ligeng; Ali, Izhar; Ullah, Saif; Wu, Xiuchan; Cao, Tianyi; Zhao, Quan; Li, Tianyuan
Abstract: Few studies have been conducted on changes in the amylose content and rapid visco‐analyzer (RVA) profile characteristics of noodle rice cultivars under different ecological conditions. This research was conducted in 2017 and 2018 to evaluate changes in amylose content and RVA profile characteristics of ten noodle rice cultivars at three test sites. The cultivars were planted in Nanning, Hengyang, and Nanchang in 2017. Four cultivars were planted at each site on seven sowing dates with an interval of 15 d in 2018. Grain amylose content and RVA profile characteristics were determined after the rice had been stored for three months. The results showed that there were significant differences between the cultivars in the amylose content and RVA profile characteristics. The RVA profile characteristics of the 10 rice cultivars did not exhibit a similar trend for the three test sites. The average coefficient of variation was 8.6% for the amylose content, greater than 25% for the breakdown (BD) and setback (SB); 10 to 20% for the consistency (CSV) and peak viscosity (PV); and less than 10% for the trough viscosity (TV), final viscosity (FV), peak time (PT), and pasting temperature (PaT). The correlation analysis showed that the amylose content was significantly correlated with the PT, TV, BD, PaT, SB, and FV. It was concluded that there were significant differences in the amylose content and RVA profile characteristics between the rice cultivars and significant genetic‐environment interaction effects. The amylose content of the special noodle rice cultivars was significantly correlated with the RVA profile characteristics.